TOURISM AS A SCIENCE OF RECREATION AND RELATIONSHIP WITH OTHER (Proceedings of the YSU C: Geological and Geographical Sciences, 2021)
The article presents the concepts of tourism. It was revealed that tourism as a frontier science is formed at the intersection of philosophy, geography, economics and other sciences. It has been substantiated that tourism is the science of the principles, approaches and methods of organizing and managing a tourist (recreational) economy.
Keywords: tourism; method; recreation mountains; rivers human capital; resource